Fourth-generation quinolones in the treatment of Helicobacter pylori infection: A meta-analysis - An, Ying (World J Gastroenterol, 2018)
AIM: To assess the efficacy and safety of fourth-generation quinolones for Helicobacter pylori (H. pylori) eradication, we conducted this systematic review and meta-analysis of randomized clinical trials. METHODS: Major literature databases (PubMed, EMBASE and the Cochrane Central Register of Controlled Trials) were searched for relevant articles published prior to February 2018. We performed a meta-analysis of all randomized clinical trials that examined the efficacy of H. pylori eradication therapies and included fourth-generation quinolones in the experimental arm. Subgroup analyses by regions and different types of fourth-generation quinolones were also performed. RESULTS: Ten studies including a total of 2198 patients were assessed. A meta-analysis of randomized controlled trials showed that the eradication rate of therapies containing non-fourth-generation quinolones was significantly lower than that of therapies containing fourth-generation quinolones by intention-to-treat (ITT) analysis [75.4% vs 81.8%; odds ratio (OR) = 0.661; 95% confidence interval (CI): 0.447-0.977; P = 0.038]. This analysis also showed that the eradication rate of the therapies containing non-fourth-generation quinolones was inferior to that of therapies containing fourth-generation quinolones by per-protocol analysis (79.1% vs 84.7%; OR = 0.663; 95%CI: 0.433-1.016; P = 0.059). Moreover, the occurrence of side effects was significantly different between the control and experimental groups by ITT analysis (30.6% vs 19.5%; OR = 1.874; 95%CI: 1.120-3.137; P = 0.017). The sub-analyses also showed significant differences in moxifloxacin therapies vs other fourth-generation quinolone therapies (84.3% vs 71.9%) and in Asian vs European groups (76.7% vs 89.1%). CONCLUSION: Therapies containing fourth-generation quinolones achieved a poor eradication rate in the treatment of H. pylori infection. Such regimens might be useful as a rescue treatment based on antimicrobial susceptibility testing. Different antibiotics should be chosen in different regions.